Mobile experimentation using modelling and simulation in the Fog/Cloud. Issue 6 (2nd November 2022) - Al-Zoubi, Khaldoon; Wainer, Gabriel
ABSTRACT: Recently, we have seen an increase of the use of Cloud computing to provide Modelling & Simulation services. In general, mobility support is lacking since clients normally contact the same centralised clouds regardless of their locations. In this research, we propose a method and algorithms to build Fog s as private services in which different middleware running in varied Virtual Machines (on various distributed Fogs and Cloud backbone) to expose different services. Clients access services via nearby Fogs, which then discover the required resources to run experiments (on Fogs or cloud backbone). Our focus is on mobility, to permit clients to conduct experiments (and visualise simulation results) using mobile devices. Mobility support is further improved by introducing the novel concept of a mobile simulation experiment : if a device moves away from a given Fog zone, the experiment moves with the device. We present a prototype implementation, evaluation results, and different case studies.